Control de arbustos en potreros : resumen de cuatro años de investigación - Argel M., Pedro J.; Doll, Jerry D. (1976)
The most serious weed problems faced by ranchers are comprised of brushy species. Foliar, cut-stump, basal and soil applications of herbicides were evaluated on the most common species on ranches of the North Coast of Colombia from 1972 through 1975. Most of the species tested were resistant to foliarly applied treatments. Casearia javitensis, young and previously uncut plants of Myrospermum frutescens, and Sida sp. were the only susceptible ones. Cut-stump treatments were effective on all species tested. Ester formulations of the herbicides were mixed with diesel fuel in concentrations of 2 to 4 percent and these controlled Cordia coloccoca, Chonelia spinosa, previously cut plants of M. frustescens, Piper marginatum, Casearia aculeata and Dipysa carthagenensis. Basal treatments to Bredemeyera floribunda gave excellent control. Applying residual herbicides such as tebuthiuron, karbutilate and DPX-3674 at the base of brush plants gave promising results. DPX-3674 was the most active due to its greater solubility but for all products complete kill was not obtained until six to 12 months after treatment.